Performance of a whole blood interferon gamma assay for detecting latent infection with Mycobacterium tuberculosis in children. Issue 7 (6th April 2006) - Connell, T G; Curtis, N; Ranganathan, S C; Buttery, J P
Abstract : Background: The diagnosis of latent Mycobacterium tuberculosis (MTB) infection with a tuberculin skin test (TST) in children is complicated by the potential influence of prior exposure to Bacille Calmette Geurin (BCG) vaccination or environmental mycobacteria. A whole blood assay has recently been developed to quantitatively measure interferon gamma (IFN-γ) production by lymphocytes specific to the MTB antigens ESAT-6 and CFP-10, but its use and assessment in children has been limited. A study was undertaken to compare the performance of the whole blood IFN-γ assay with the TST in diagnosing latent tuberculosis (TB) infection or TB disease in children in routine clinical practice. Methods: One hundred and six children with a high risk of latent TB infection or TB disease were enrolled in the study. High risk was defined as contact with TB disease, clinical suspicion of TB disease, or recent arrival from an area of high TB prevalence. The whole blood IFN-γ assay was undertaken in 101 children. Results: Seventeen (17%) of the 101 assays yielded inconclusive results due to failure of positive or negative control assays. There was poor correlation between the whole blood IFN-γ assay and the TST (kappa statistic 0.3) with 26 (70%) of the 37 children defined as latent TB infection by TST having a negative whole blood IFN-γ assay. There were no instances of a positive whole blood IFN-γ assay with a negative TST. Mitogen (positive) control IFN-γ responses were significantly correlated with age (Spearman's coefficient = 0.53, p<0.001) and, in children with latent TB infection identified by TST, those with a positive IFN-γ assay were older (median 12.9 v 6.92 years, respectively, p = 0.007). The whole blood IFN-γ assay was positive in all nine children with TB disease. Conclusion: There was poor agreement between the whole blood IFN-γ assay and TST for the diagnosis of latent TB. The whole blood IFN-γ assay may have lower sensitivity than the TST in diagnosing TB infection in children. A significant proportion of whole blood IFN-γ assays fail when used as a screening assay in routine practice.